Basement Membrane of Tissue Engineered Extracellular Matrix Scaffolds Modulates Rapid Human Endothelial Cell Recellularization and Promote Quiescent Behavior After Monolayer Formation - Lopera Higuita, Manuela; Shortreed, Nicholas A.; Dasari, Surendra; Griffiths, Leigh G. (Frontiers in Bioengineering and Biotechnology, 2022)
Off-the shelf small diameter vascular grafts are an attractive alternative to eliminate the shortcomings of autologous tissue for vascular grafting. Bovine saphenous vein (SV) extracellular matrix (ECM) scaffolds are potentially ideal small diameter vascular grafts, due to their inherent architecture and signaling molecules capable of driving repopulating cell behavior and regeneration. However, harnessing this potential is predicated on the ability of the scaffold generation technique to maintain the delicate structure, composition and associated function of native vascular ECM. Previous decellularization methods have been uniformly demonstrated to disrupt the delicate basement membrane components of native vascular ECM. The Antigen Removal (AR) tissue processing method utilizes protein chemistry principle of differential solubility to achieve a step-wise removal of antigens with similar physiochemical properties. Briefly, cellular components of SV are permeabilized and actomyosin crossbridges relaxed, followed by lipophilic antigen removal, sarcomeric disassembly, hydrophilic antigen removal, nuclease digestion and washout. Here we demonstrate bovine SV ECM scaffolds generated using the novel AR approach results in retention of native basement membrane protein structure, composition (e.g., Collagen IV and laminin) and associated cell modulatory function. Presence of basement membrane proteins in AR vascular ECM scaffolds increases rate of endothelial cell monolayer formation by enhancing cell migration and proliferation. Following monolayer formation, basement membrane proteins promote appropriate formation of adherence junction and apicobasal polarization, increasing secretion of nitric oxide, and driving repopulating endothelial cells toward a quiescent phenotype. We conclude that presence of intact native vascular basement membrane in AR SV ECM scaffolds modulates human endothelial cell quiescent monolayer formation which is essential for vessel homeostasis.